Noise-Reduced WSe2 Phototransistors for Enhanced Photodetection Performance via Suppression of Metal-Induced Gap States - Ryoo, Sunggyu; Sim, Jinwoo; Jeong, Seungjun; Jang, Juntae; Woo, Jaeyong; Park, Jaehyoung; Ko, Seongmin; Kim, Yeeun; Song, Youngmin; Yoo, Jongeun; Ahn, Heebeom; Kang, Keehoon; et al. (JOHN WILEY & SONS INC, 2025)
Phototransistors are critical components in optoelectronics, and 2D transition metal dichalcogenides (TMDC), such as tungsten diselenide (WSe2), show promise for phototransistor applications due to their strong light-matter interaction, unique excitonic properties, and high surface-to-volume ratio. In 2D TMDC-based phototransistors, 1/f noise, caused by complex defect states, acts as a dominant low-frequency noise (LFN) and is crucial for obtaining accurate photodetection characteristics. However, many studies still overlook LFN and focus on enhancing photocurrent or response time. In this study, the importance of LFN analysis is highlighted in WSe2 phototransistors and demonstrate reduced noises and enhanced photodetection performance through the suppression of metal-induced gap states (MIGS) that act as noise sources by utilizing semimetal bismuth (Bi) contact. The WSe2 phototransistors demonstrated approximate to 1000 times lower noise, 100 times higher responsivity, and 10 times higher specific detectivity than devices with conventional metal contacts. The results of this study suggest that reducing LFN in photodetection devices, such as by suppressing MIGS, can be an efficient way to enhance device performance.